Removal of Pollutants from Industrial Effluents Using Plastic Clay and Pyrophyllite - Rai, Kalpna; Maheshwari, A. (Asian Journal of Chemistry, 2010)
Attempts were made to remove Cr(VI) from tannery effluents, PO3–4 from gelatin industry effluent and C2O2–4 from oxalic acid manufacturing unit effluent by plastic clay and pyrophyllite adsorbent. The adsorption of Cr(VI), PO3–4 and C2O2–4 was found to be appreciable in both adsorbents but removal was higher in plastic clay for Cr(VI) and C2O2–4 . Removal of PO3–4 was higher on pyrophyllite. The percentage removal of Cr(VI). PO3–4 and C2O2–4 in industrial waste waters was 43.8, 49.6 and 53.4 on plastic clay and 21.9. 53.1. 34.3 on pyrophyllite respectively. The equilibrium data fit well within the Langmuir and Freundlich isotherms.